High temperature stable optically clear pressure sensitive adhesive
Patent Information
- Application Number
- CN202180075596.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-16
- Filing Date
- 2021-11-09
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-11-09
AI Technical Summary
[0004]还公开了粘合剂制品,其包括至少一个基底和设置在该基底上的如上所述的压敏层。
Smart Images

Figure BDA0004218443150000091 
Figure BDA0004218443150000121 
Figure BDA0004218443150000151
Abstract
Description
Background Technology
[0001] Adhesives are used for a variety of marking, fixing, protection, sealing, and masking applications. Adhesive tapes generally consist of a backing or substrate and an adhesive. One type of adhesive, pressure-sensitive adhesive, is particularly preferred for many applications.
[0002] Pressure-sensitive adhesives are well known to those skilled in the art and possess certain properties at room temperature, including: (1) strong and durable tack, (2) adhesion by finger pressure, (3) sufficient ability to hold onto the adhesive, and (4) sufficient cohesive strength for clean removal from the adhesive. Materials found to be well-suited for use as pressure-sensitive adhesives are polymers designed and formulated to exhibit the desired viscoelastic properties, thereby achieving a desired balance between tack, peel adhesion, and shear strength. The most commonly used polymers for preparing pressure-sensitive adhesives are natural rubber, synthetic rubbers (e.g., styrene / butadiene copolymers (SBR) and styrene / isoprene / styrene (SIS) block copolymers), various (meth)acrylates (e.g., acrylate and methacrylate copolymers), and silicones. Each of these types of materials has its own advantages and disadvantages. Summary of the Invention
[0003] This document discloses a high-temperature stable, optically transparent pressure-sensitive adhesive. In some embodiments, the pressure-sensitive adhesive composition comprises a (meth)acrylate polymer or copolymer matrix and at least one high-temperature stabilizer. The (meth)acrylate polymer or copolymer matrix comprises a reaction product of at least one (meth)acrylate monomer containing at least one hydroxyl group. The pressure-sensitive adhesive composition is optically transparent, and when exposed to a temperature of at least 85°C for 7 days, the increase in cohesive strength, as measured by stress relaxation, is 0.1 or less.
[0004] An adhesive article is also disclosed, comprising at least one substrate and a pressure-sensitive layer disposed on the substrate as described above. Detailed Implementation
[0005] Adhesives are used for a wide range of marking, fixing, protection, sealing, and masking applications. One class of adhesives, pressure-sensitive adhesives (PSAs), is particularly useful for many applications. The use of adhesives, especially PSAs, is increasing in fields such as the medical, electronics, and optics industries. These industries place additional demands on PSAs beyond conventional tack, peel strength, and shear strength. To meet the increasingly stringent performance requirements for PSAs, various new materials are needed. Additional requirements for PSAs include optical properties such as transparency and high flexibility. Maintaining these properties throughout the product's lifespan and under a range of aging conditions, such as high-temperature aging, is also becoming increasingly important.
[0006] Among the pressure-sensitive adhesives widely used in optical applications are (meth)acrylate-based pressure-sensitive adhesives. These adhesives comprise a polymer or copolymer matrix containing at least one (meth)acrylate monomer, and may contain additional (meth)acrylate monomers and additional olefinically unsaturated monomers. Typically, acidic monomers such as acrylic acid or methacrylic acid are incorporated into the (meth)acrylate-based matrix to improve the cohesive strength of the matrix. Since some optical products include an acid-sensitive layer accessible to the adhesive layer, acid-free (meth)acrylate pressure-sensitive adhesives have been developed.
[0007] It has been observed that (meth)acrylate-based pressure-sensitive adhesives exhibit an increase in cohesive strength upon exposure to elevated temperatures. This is thought to be due to the formation of crosslinks between the polymers in the (meth)acrylate composition. Such crosslinking can be achieved through the reaction of a carboxylic acid group on one polymer with an alcohol on another polymer (as shown in the Fischer esterification reaction) or through an transesterification reaction (as shown below).
[0008] R p1 -C(O)-OH+R p2 -C(O)-R'-OH→R p1 -C(O)-O-R'-C(O)-R p2 +H2O
[0009] Fischer esterification
[0010] In this exemplary reaction, C(O) is a carbonyl group -C=O, and group R p1 and R p2 This refers to a (meth)acrylate polymer chain, where R' is an alkylene group. It is clear from this reaction that an acid group on one polymer chain can react with a hydroxyl group on another polymer chain, thereby forming crosslinks between the polymer chains.
[0011] R p1 -C(O)-OR a +R p2 -C(O)-R'-OH→R p1 -C(O)-O-R'-C(O)-R p2 +R a -OH
[0012] transesterification
[0013] In this exemplary reaction, C(O) is a carbonyl group -C=O, and group R p1 and R p2 It refers to a (meth)acrylate polymer chain, where R' is an alkylene group, and R aThe alkyl group may or may not be hydroxyl-functional. It is clear from this reaction that a hydroxyl group on one polymer chain can attack the ester bond of another polymer chain to form crosslinks between the polymer chains.
[0014] These crosslinking reactions increase the cohesive strength of the pressure-sensitive adhesive. In many applications, this increase in cohesive strength is not necessarily a problem, but in applications where high flexibility of the pressure-sensitive adhesive layer is desired, the increased cohesive strength can be a major issue. These crosslinking reactions are undesirable if the pressure-sensitive adhesive is expected or required to remain flexible, allowing articles containing the adhesive layer to be bent, folded, or rolled.
[0015] One method for suppressing Fischer esterification is to add an acid-scavenging agent to the polymer composition to block the reaction between acidic and alcoholic groups. However, as mentioned above, some acid-free (meth)acrylate adhesives have been developed. Although these adhesives do not undergo Fischer esterification, they still undergo transesterification crosslinking. Therefore, it is expected that adding an acid-scavenging agent to the pressure-sensitive adhesive composition will not affect the transesterification crosslinking reaction.
[0016] It has been observed that the cohesive strength of (meth)acrylate pressure-sensitive adhesives containing hydroxyl groups but lacking acid groups also increases upon exposure to elevated temperatures. As mentioned above, the addition of materials intended as deacidifying agents is not expected to suppress the increase in cohesive strength of these pressure-sensitive adhesives. Surprisingly, it was found that the addition of hydrotalcite or carbodiimide suppressed the increase in cohesive strength of these pressure-sensitive adhesives. Furthermore, the addition of hydrotalcite or carbodiimide also suppressed the increase in cohesive strength in these compositions if acid groups are present in the pressure-sensitive adhesive.
[0017] Unless otherwise specified, all figures used in the specification and claims to express structural dimensions, quantities, and physical properties should in all cases be understood to be modified by the term "about". Therefore, unless stated to the contrary, the numerical parameters listed in the foregoing specification and appended claims are approximations, which may vary according to the desired properties sought by a person skilled in the art using the teachings disclosed herein. Numerical ranges expressed in terms of endpoints include all numbers contained within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, and 5) and any range within that range.
[0018] Unless otherwise expressly stated, as used in this specification and the appended claims, the singular forms “a,” “an,” and “described” cover embodiments having multiple referents. For example, the reference to “a layer” covers embodiments having one layer, two layers, or more layers. Unless otherwise expressly stated, as used in this specification and the appended claims, the term “or” is generally used in a meaning that includes “and / or.”
[0019] As used herein, the term "adhesive" refers to a polymer composition that can be used to adhere two adhesives together. An example of an adhesive is a pressure-sensitive adhesive.
[0020] Those skilled in the art are well aware that pressure-sensitive adhesive compositions possess properties including (1) strong and durable tack, (2) adhesion upon finger pressure, (3) sufficient ability to hold onto the adhesive, and (4) sufficient cohesive strength for clean removal from the adhesive. Materials found to be well-suited for use as pressure-sensitive adhesives are polymers designed and formulated to exhibit the desired viscoelastic properties, thereby achieving a desired balance between tack, peel adhesion, and shear retention. Achieving this proper balance of properties is not a simple matter.
[0021] The term "(meth)acrylate" refers to the monomeric acrylate or methacrylate of an alcohol. Acrylates and methacrylate monomers or oligomers are collectively referred to herein as "(meth)acrylate". As used herein, a material referred to as "(meth)acrylate group" is a polymer containing at least a majority of (meth)acrylate units, but may also contain additional units derived from other olefinic unsaturated groups.
[0022] The terms "room temperature" and "ambient temperature" are used interchangeably, referring to temperatures in the range of 20°C to 25°C.
[0023] The terms "Tg" and "glass transition temperature" are used interchangeably. If measured, unless otherwise specified, the Tg value is determined by differential scanning calorimetry (DSC) at a scan rate of 10 °C / min. Typically, the Tg value of the copolymer is not measured; instead, it is calculated using the well-known Fox formula, using the monomer Tg values provided by the monomer supplier, as understood by those skilled in the art.
[0024] As used herein, the term "adjacent" in the context of two floors means that the two floors are adjacent to each other and there is no intervening opening space between them. They may be in direct contact with each other (e.g., stacked together) or there may be an intervening floor.
[0025] As used herein, the terms “polymer” and “macromolecule” are consistent with their common usage in chemistry. Polymers and macromolecules are composed of many repeating subunits. As used herein, the term “macromolecule” is used to describe a group attached to a monomer that has multiple repeating units. The term “polymer” is used to describe the material obtained by a polymerization reaction.
[0026] The term "alkyl" refers to a monovalent group that is an alkane group, where the alkane is a saturated hydrocarbon. Alkyl groups can be straight-chain, branched, cyclic, or combinations thereof, and typically have 1 to 20 carbon atoms. In some embodiments, the alkyl group contains 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, and ethylhexyl ester.
[0027] The term "aryl" refers to a monovalent group consisting of an aromatic ring and a carbocyclic ring. An aryl group can have one to five rings attached to or fused with an aromatic ring. Other ring structures can be aromatic, non-aromatic, or combinations thereof. Examples of aryl groups include, but are not limited to, phenyl, biphenyl, terphenyl, anthryl, naphthyl, acenaphthenic, anthraquinone, phenanthryl, anthracenyl, pyrene, peryl, and fluorenyl.
[0028] The term "alkanediol" refers to a divalent group that is a group of an alkane. Alkanediols can be straight-chain, branched, cyclic, or a combination thereof. Alkanediols typically have 1 to 20 carbon atoms. In some embodiments, alkanediols contain 1 to 18, 1 to 12, 1 to 10, 1 to 8, 1 to 6, or 1 to 4 carbon atoms. The group center of the alkanediol can be on the same carbon atom (i.e., an alkylidene group) or on different carbon atoms.
[0029] The terms “radical polymerizable” and “olefinic unsaturated” are used interchangeably and refer to reactive groups containing carbon-carbon double bonds capable of polymerization via a radical polymerization mechanism.
[0030] Unless otherwise specified, the terms "optically transparent" and "visible light transmittance" are used interchangeably and refer to articles, films, or adhesives having high transmittance over at least a portion of the visible light spectrum (about 400 nm to about 700 nm). Typically, optically transparent articles have at least 90% visible light transmittance and a haze of equal to or less than 10%.
[0031] Unless otherwise specified, "optically clear" means an adhesive or article that has high transmittance and exhibits low haze (typically less than about 5%, or even less than about 2%) over at least a portion of the visible light spectrum (about 400 nm to about 700 nm). In some embodiments, optically clear articles exhibit haze of less than 1% or even 0.5% at a thickness of 50 micrometers. Typically, optically clear articles have at least 95%, and typically higher, such as 97%, 98%, or even 99% or higher, visible light transmittance.
[0032] This document discloses a pressure-sensitive adhesive composition with improved high-temperature stability. In some embodiments, the pressure-sensitive adhesive composition comprises a (meth)acrylate polymer or copolymer matrix and at least one high-temperature stabilizer. The (meth)acrylate polymer or copolymer matrix comprises a reaction product of at least one (meth)acrylate monomer containing at least one hydroxyl group. The pressure-sensitive adhesive composition is optically transparent and, when exposed to a temperature of at least 85°C for 7 days, exhibits an increase in cohesive strength measured by stress relaxation of 0.1 or less.
[0033] A wide range of polymer or copolymer matrices are suitable for use in the pressure-sensitive adhesive compositions of the present invention. The polymer or copolymer matrix is prepared by polymerizing a reaction mixture comprising at least a (meth)acrylate monomer. This reaction mixture may also contain additional monomers as described below, optional crosslinking agents as described below, and at least one initiator (typically a photoinitiator).
[0034] The polymer or copolymer matrix comprises at least one monomer having a hydroxyl functional group. In some embodiments, the polymer or copolymer matrix is a reaction product of a (meth)acrylate monomer of Formula 1:
[0035] H2C = CR 1 -(CO)-O-(CH2) a -OH
[0036] Formula 1
[0037] Where R 1 H or methyl, (CO) is a carbonyl C=O, and a is an integer from 1 to 5. Examples of suitable (meth)acrylate monomers of formula 1 include HEA (hydroxyethyl acrylate), HEMA (hydroxyethyl methacrylate), hydroxypropyl acrylate, and HBA (hydroxybutyl acrylate).
[0038] In many embodiments, the polymer or copolymer matrix is a copolymer matrix comprising a (meth)acrylate monomer of Formula 1 above and at least one additional (meth)acrylate monomer of Formula 2. Typically, the additional monomer includes alkyl (meth)acrylate, aryl (meth)acrylate, or acrylic acid.
[0039] H2C = CHR 1 -(CO)-OR 2
[0040] Formula 2
[0041] Where R 1 It is a hydrogen atom or a methyl group, (CO) is a carbonyl group C=O, and R 2 It is a hydrogen atom, an alkyl group having 4 to 20 carbon atoms, or an aryl group. Typically, one or more additional monomers are alkyl (meth)acrylates and / or acrylic acid. As described above, the alkyl group of the (meth)acrylate has an average of about 4 to about 20 carbon atoms, or an average of about 4 to about 14 carbon atoms. The alkyl group may optionally contain an oxygen atom in the chain, thereby forming, for example, an ether or an alkoxy ether. Examples of monomer A include, but are not limited to, 2-methylbutyl acrylate, isooctyl acrylate, lauryl acrylate, 4-methyl-2-pentyl acrylate, isoamyl acrylate, sec-butyl acrylate, n-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, isodecanyl acrylate, isodecanyl methacrylate, and isononyl acrylate. Other examples include (but are not limited to) polyethoxylated or polypropoxylated methoxy (meth)acrylates, such as acrylates of CARBOWAX (commercially available from Union Carbide) and NK ester AM90G (commercially available from Shin Nakamura Chemical, Ltd., Japan). Particularly suitable alkyl (meth)acrylates include isooctyl acrylate, 2-ethylhexyl acrylate, n-hexyl acrylate, and n-butyl acrylate. Copolymers can be prepared using various combinations of monomers.
[0042] Generally, (meth)acrylate copolymers are formulated to have a resulting Tg of less than about 0°C, more typically less than about -10°C. Such acrylate copolymers typically contain at least one monomer of formula 1 in about 1 / 100 parts to about 40 / 100 parts and at least one monomer of formula 2 in about 99 / 100 parts to about 60 / 100 parts.
[0043] Crosslinking agents can be used to construct the molecular weight and strength of (meth)acrylate copolymers. Typically, crosslinking agents are those that copolymerize with monomers of Formula 1 and Formula 2. Suitable crosslinking agents are disclosed in U.S. Patents 4,737,559 (Kellen), 5,506,279 (Babu et al.), and 6,083,856 (Joseph et al.). Crosslinking agents can be photocrosslinking agents, inducing crosslinking of the copolymer when exposed to ultraviolet radiation (e.g., radiation with wavelengths from about 250 nm to about 400 nm). An example of a suitable photocrosslinking agent is ABP (benzophenone acrylate).
[0044] The crosslinking agent is used in an effective amount, which means an amount sufficient to cause the pressure-sensitive adhesive to crosslink and provide sufficient cohesive strength to produce the desired final adhesion properties on the substrate of interest. Generally, the amount of crosslinking agent used is from about 0.1 parts to about 10 parts based on the total amount of monomers.
[0045] One class of available crosslinking agents includes polyfunctional (meth)acrylate substances. Polyfunctional (meth)acrylates include tri(meth)acrylates and di(meth)acrylates (i.e., compounds containing three or two (meth)acrylate groups). Typically, di(meth)acrylate crosslinking agents (i.e., compounds containing two (meth)acrylate groups) are used. Available tri(meth)acrylates include, for example, trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, tri(2-hydroxyethyl)isocyanurate triacrylate, and pentaerythritol triacrylate. Available di(meth)acrylates include, for example, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, alkoxylated 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, dipropylene glycol diacrylate, cyclohexanediol di(meth)acrylate, alkoxylated cyclohexanediol diacrylate, ethoxylated bisphenol A di(meth)acrylate, neopentyl glycol diacrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and urethane di(meth)acrylate.
[0046] Another class of crosslinking agents available contains functional groups that react with carboxylic acid groups on acrylic copolymers in the presence of carboxylic acid groups. Examples of such crosslinking agents include polyfunctional aziridines, isocyanates, epoxy resins, and carbodiimide compounds. Examples of aziridine-type crosslinking agents include, for example, 1,4-bis(ethyleneiminocarbonylamino)benzene, 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane, 1,8-bis(ethyleneiminocarbonylamino)octane, and 1,1'-(1,3-phenylene dicarbonyl)-bis-(2-methylaziridine). The aziridine crosslinking agent 1,1'-(1,3-phenylene dicarbonyl)-bis-(2-methylaziridine), often referred to as a "diamide," is particularly available. Common polyfunctional isocyanate crosslinking agents include, for example, trimethylolpropane toluene diisocyanate, toluene diisocyanate, and hexamethylene diisocyanate.
[0047] The reaction mixture also contains at least one initiator. Typically, one or more initiators include a photoinitiator, meaning the initiator is activated by light, typically ultraviolet (UV) light. Examples of suitable free radical photoinitiators include DAROCURE 4265, IRGACURE 184, IRGACURE 651, IRGACURE 1173, IRGACURE 819, LUCIRIN TPO, and LUCIRIN TPO-L, commercially available from BASF, Charlotte, NC, North Carolina. Generally, the photoinitiator is used in amounts from 0.01 parts by weight to 1 part by weight relative to 100 parts by weight of total reactive components.
[0048] A polymer or copolymer matrix is prepared by polymerizing a reactive mixture made from monomers or monomer mixtures, optionally a crosslinking agent, and at least one initiator (typically a photoinitiator). The reactive composition components can be mixed using conventional methods known to those skilled in the art. Such methods include mixing, mechanical rolling, hot melt blending, etc.
[0049] The polymer or copolymer matrix can be prepared by bulk polymerization or by coating and curing methods. In many embodiments, the method for preparing the pressure-sensitive adhesive matrix includes a coating and curing process. This method includes preparing a reactive mixture, partially curing the mixture to form a curable, coatable slurry, coating the slurry onto a substrate to form a curable layer, covering the curable layer with a release liner, and polymerizing the curable layer to form a cured layer. This method is described, for example, in U.S. Patent 6,339,111 (Moon et al.).
[0050] The pressure-sensitive adhesive composition also contains at least one high-temperature stabilizer. Typically, high-temperature stabilizers are materials used as acid scavengers. However, not all materials commonly used as acid scavengers are suitable. Commonly used acid scavengers include epoxy compounds, tertiary amines, hydrotalcite, and carbodiimide. Suitable high-temperature stabilizers in this disclosure are hydrotalcite and carbodiimide.
[0051] Hydrotalcite has the general formula Mg6Al2CO3(OH). 16 The layered binary hydroxide of 4(H2O) is named for its similarity to talc and its high water content.
[0052] A wide range of carbodiimides are suitable high-temperature stabilizers. Carbodiimides (IUPAC name: methanediimide) are compounds having the general formula 3:
[0053] R a -N=C=NR b
[0054] Formula 3
[0055] Group R a and R b They can be the same or different, and include a wide range of alkyl, substituted alkyl, aryl, or substituted aryl groups. Particularly suitable are carbodiimides, wherein the group R... a and R b It is a substituted aryl group. A particularly suitable carbodiimide is bis(2,6-diisopropylphenyl)carbodiimide (structure shown below).
[0056]
[0057] In some embodiments, the high-temperature stabilizer includes hydrotalcite. Because hydrotalcite is an inorganic material, it is insoluble in the (meth)acrylate matrix and tends to form particles within the matrix. The presence of these hydrotalcite particles increases the haze of the pressure-sensitive adhesive. The pressure-sensitive adhesive is optically transparent, with at least 90% visible light transmittance and less than 10% haze.
[0058] In other embodiments, the high-temperature stabilizer includes carbodiimide. Carbodiimide is an organic material and soluble in a (meth)acrylate matrix. This pressure-sensitive adhesive is not only optically transparent, with at least 90% visible light transmittance and less than 10% haze, but also optically clear, with at least 95% visible light transmittance and less than 5% haze. In some embodiments, the carbodiimide includes bis(2,6-diisopropylphenyl)carbodiimide.
[0059] Regardless of the type of high-temperature stabilizer used, it is present in small amounts. In some embodiments, the content of the high-temperature stabilizer in the adhesive composition is from 0.1% to 5% by weight. In some embodiments, the content of the high-temperature stabilizer in the adhesive composition is from 0.5% to 3% by weight, or even from 1% to 2% by weight.
[0060] Typically, pressure-sensitive adhesive compositions are stable for 7 days at a temperature of at least 85°C. Herein, stability refers to the suppression of the increase in cohesive strength of the pressure-sensitive adhesive through increased crosslinking. The suppression of the increase in cohesive strength of the pressure-sensitive adhesive can be measured in a variety of ways. A particularly suitable method is to measure the increase in cohesive strength by measuring stress relaxation. In some embodiments, the pressure-sensitive adhesive of this disclosure exhibits an increase in stress relaxation of 0.1 or less after exposure to a temperature of at least 85°C for 7 days. Stress relaxation can be measured using a rheometer. Stress relaxation is a measure of how much stress is released after a certain level of stress has been applied for a period of time. Stress relaxation is typically reported as the ratio of initial stress to final stress.
[0061] This document also discloses adhesive articles. In some embodiments, the adhesive article includes: a substrate comprising a first main surface and a second main surface; and an adhesive layer disposed on at least a portion of the second main surface of the substrate. The adhesive layer comprises a pressure-sensitive adhesive as described above. In some embodiments, the adhesive layer comprises a (meth)acrylate polymer or copolymer matrix and at least one high-temperature stabilizer, wherein the (meth)acrylate polymer or copolymer matrix comprises a reaction product of at least one (meth)acrylate monomer containing at least one hydroxyl group. The pressure-sensitive adhesive composition is optically transparent and, when exposed to a temperature of at least 85°C for 7 days, exhibits an increase in cohesive strength measured by stress relaxation of 0.1 or less.
[0062] As described above, in many embodiments, (meth)acrylate is the copolymer matrix and optionally contains a crosslinking agent, said copolymer matrix comprising a copolymer matrix as a reaction product of a (meth)acrylate monomer of Formula 1 and at least one (meth)acrylate monomer of Formula 2.
[0063] As described above, in some embodiments, the high-temperature stabilizer includes hydrotalcite or carbodiimide. Compositions containing hydrotalcite are optically transparent, while compositions containing carbodiimide are optically clear.
[0064] A wide range of substrates are suitable for the articles of manufacture disclosed herein. Typically, the substrate comprises a polymer film or a release liner. Examples of polymer films include films comprising one or more polymers such as cellulose acetate butyrate; cellulose acetate propionate; cellulose triacetate; poly(meth)acrylates, such as polymethyl methacrylate; polyesters, such as polyethylene terephthalate and polyethylene naphthalate; copolymers or blends based on naphthalene dicarboxylic acid; polyethersulfone; polyurethane; polycarbonate; polyvinyl chloride; syndiotactic polystyrene; cycloolefin copolymers; and polyolefins, including polyethylene and polypropylene, such as cast and biaxially oriented polypropylene. The substrate may comprise a single layer or multiple layers, such as polyethylene-coated polyethylene terephthalate. The substrate may be primed or treated to impart desired properties to one or more of its surfaces. Examples of such treatments include corona treatment, flame treatment, plasma treatment, and chemical treatment.
[0065] One particularly suitable type of film substrate is optical film. As used herein, the term "optical film" refers to a film that can be used to produce optical effects. Optical films are typically polymer-containing films, which can be single-layered or multi-layered. Optical films can have any suitable thickness. Optical films are typically at least partially transmissive, reflective, antireflective, polarized, optically sharp, or diffuse relative to certain wavelengths of the electromagnetic spectrum (e.g., wavelengths in the visible, ultraviolet, or infrared regions of the electromagnetic spectrum). Exemplary optical films include, but are not limited to, viewing mirror films, colored mirror films, sunlight-reflective films, diffused films, infrared-reflective films, ultraviolet-reflective films, reflective polarized films such as brightness enhancement films and double-layer brightness enhancement films, absorptive polarized films, optically sharpening films, colored films, tinted films, privacy films such as light-calibrating films, as well as antireflective films, anti-glare films, anti-fouling films, and anti-fingerprint films.
[0066] Some optical films have multiple layers, such as multiple layers containing polymeric materials (e.g., polymers with or without dyes), or multiple layers containing metallic and polymeric materials. Some optical films have alternating layers of polymeric materials with different refractive indices. Other optical films have alternating polymeric and metallic layers. Exemplary optical films are described in the following patents: U.S. Patent No. 6,049,419 (Wheatley et al.); U.S. Patent No. 5,223,465 (Wheatley et al.); U.S. Patent No. 5,882,774 (Jonza et al.); U.S. Patent No. 6,049,419 (Wheatley et al.); U.S. Patent No. RE 34,605 (Schrenk et al.); U.S. Patent No. 5,579,162 (Bjornard et al.); and U.S. Patent No. 5,360,659 (Arends et al.).
[0067] In some embodiments, the first carrier layer is a release liner. Exemplary release liners include those made of paper (e.g., kraft paper) or polymeric materials (e.g., polyolefins such as polyethylene or polypropylene, ethylene vinyl acetate, polyurethane, polyesters such as polyethylene terephthalate, etc., and combinations thereof). At least some release liners are coated with a release agent layer, such as a silicone-containing material or a fluorocarbon-containing material. Exemplary release liners include, but are not limited to, liners commercially available under the trade names “T-30” and “T-10” from CP Film, Martinsville, Va., which have a silicone release coating on a polyethylene terephthalate film.
[0068] Example
[0069] These examples are for illustrative purposes only and are not intended to limit the scope of the appended claims. Unless otherwise specified, all parts, percentages, ratios, etc., in the examples and the remainder of the specification are by weight. Unless otherwise specified, all solvents and other reagents used were obtained from Sigma-Aldrich Chemical; Milwaukee, Wisconsin. The following abbreviations are used herein: sec = second; nm = nanometer; cm = centimeter; mW = milliwatt; the terms "% by weight", "% by weight", and "wt%" are used interchangeably.
[0070] Table A: Adhesive Composition Components
[0071]
[0072] Test methods
[0073] Stress relaxation
[0074] Stress relaxation is defined as the release of stress when a specific level of stress is applied for a specific time period. Stress relaxation is reported as the ratio of the final stress to the storage modulus of the initial stress, where the initial stress is 0.1 seconds, the final stress is 300 seconds, and the stress is 25% of the strain. Stress was applied at 70°C to a sample with a 20 mm diameter and a 500 μm thick adhesive (prepared by bonding adhesive sample layers together) using a DHR or ARES series rheometer from TA Instruments. The initial and final stress values were recorded, and the stress relaxation rate was calculated as the stress at 300 seconds / the stress at 0.1 seconds. A higher stress relaxation number indicates higher cohesion or a more highly cross-linked adhesive.
[0075] Haze measurement
[0076] The haze of the adhesive / glass laminate was measured using a BYK Hazegard spectrophotometer.
[0077] Preparation of adhesive samples :
[0078] All adhesive samples were prepared as follows: UV prepolymerization (0.6 mW / cm) 2 The mixture (10-minute N2 purging, ΔT 8°C) and additives are mixed to form a coatable slurry, which is then coated to a thickness of 50 micrometers on a 75-micrometer-thick siliconized PET (polyethylene terephthalate) film, covered with another 75-micrometer-thick siliconized PET (polyethylene terephthalate) film, and cured with 1 to 10 mW of 365 nm UV radiation.
[0079] Comparative Examples C1-C4 :
[0080] Adhesive samples were prepared as described above using the formulations shown in Table 1 below, and their aging properties were tested at different times and temperatures to demonstrate the problem of increased stress relaxation, which is evidence of crosslinking. Comparative examples C1-C4 were tested at 85°C for 7 days and are shown in Table 3.
[0081] Table 1: Comparison of adhesive formulations
[0082] HA 80 80 80 EHA 80 HBA 20 20 20 20 HEA Initiator-1 0.03 0.03 0.03 0.03 Initiator-2 0.25 0.25 0.25 Initiator-3 0.25 silane 0.1 0.1 0.1 UA 0.1 0.1 0.1 0.1
[0083] Comparative Examples C5-C11 :
[0084] Adhesive samples were prepared as described above using the formulations shown in Table 4 below, and their aging properties were tested. Comparative examples C5-C11 were tested at 85°C for 7 days, as shown in Table 2.
[0085] Table 2: Comparison of adhesive formulations
[0086] HA 90 100 80 80 80 80 70 EHA HBA 10 20 20 20 HEA EHMA AcM IBXA 20 NNDMA 30 Initiator-1 0.03 0.03 0.03 0.03 0.03 0.03 0.03 Initiator-2 0.25 0.25 0.25 0.25 0.25 0.25 0.25 Initiator-3 silane 0.1 0.1 0.1 0.1 0.1 0.1 0.1 UA 0.1 0.1 0.1 0.1 0.1 0.1 0.1 HDDA AA 0.1 0.2 0.3
[0087] Table 3: Stress relaxation changes after 7 days at 85℃
[0088] C1 0.209 0.319 0.110 C2 0.205 0.310 0.105 C3 0.043 0.248 0.205 C4 0.231 0.333 0.102 C5 0.040 0.071 0.031 C6 0.001 0.001 0.000 C7 0.201 0.535 0.334 C8 0.198 0.723 0.525 C9 0.200 0.663 0.463 C10 0.442 0.411 -0.031 C11 0.382 0.338 -0.044
[0089] Comparative Examples C12-C10 :
[0090] A range of amine compounds, various types of amino acrylates, free radical scavengers, hindered amine light stabilizers, and triethylamine were investigated to prevent or delay the esterification reaction between hydroxyl groups and acids, but none of them were effective.
[0091] Adhesive samples were prepared as described above using the formulations shown in Table 4 below, and their aging properties were tested. Comparative examples C12-C19 were tested at 85°C for 7 days, as shown in Table 5.
[0092] Table 4: Comparison of adhesive formulations
[0093] HA 80 80 80 80 80 80 80 80 HBA 20 20 20 20 20 20 20 20 Initiator-1 0.03 0.03 0.03 0.03 0.03 0.03 0.03 0.03 Initiator-2 0.25 0.25 0.25 0.25 0.25 0.25 0.25 0.25 silane 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 UA 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 AO 0.4 HALS-1 0.5 HALS-2 0.5 TEA 0.05 AcM 1 DMAEA 2 NNDMA 1 DMAPMA 2
[0094] Table 5: Stress relaxation changes after 7 days at 85℃
[0095] C12 0.191 0.290 0.099 C13 0.191 0.305 0.114 C14 0.170 0.276 0.106 C15 0.181 0.388 0.207 C16 0.240 0.394 0.154 C17 0.205 0.298 0.093 C18 0.219 0.316 0.097 C19 0.315 0.678 0.363
[0096] Example
[0097] Table B: High Temperature Stabilizers
[0098]
[0099]
[0100] Examples E1-E5 and Comparative Examples C20-C23
[0101] Adhesive samples containing the high-temperature stabilizers of this disclosure as described above were prepared using the formulations shown in Table 6 below, and their aging performance was tested. Examples E1-E5 and Comparative Examples C20-C23 were tested at 85°C for 7 days and are shown in Table 7. Haze values for Examples E1 and E2 are listed, where the use of hydrotalcite resulted in an increase in formulation haze. Although the haze of the examples without hydrotalcite was not measured, the samples visually exhibited significantly unchanged low haze compared to the underlying optically clear adhesives, and were estimated to have a haze of less than 1%.
[0102] Table 6: Adhesive Formulations with Stabilizers
[0103]
[0104]
[0105] NM = Not measured
[0106] Table 7: Stress relaxation changes after 7 days at 85℃
[0107] E1 0.430 0.540 0.110 E2 0.440 0.490 0.050 E3 0.211 0.265 0.054 E4 0.223 0.255 0.032 C20 0.206 0.317 0.111 C21 0.223 0.347 0.124 C22 0.199 0.294 0.169 C23 0.233 0.844 0.611 E5 0.213 0.258 0.045
Claims
1. A pressure-sensitive adhesive composition comprising: (Meth)acrylate polymer or copolymer matrix, said (meth)acrylate polymer or copolymer matrix comprising a reaction product of at least one (meth)acrylate monomer containing at least one hydroxyl group; and At least one high-temperature stabilizer, said at least one high-temperature stabilizer comprising thermally stabilized hydrotalcite or bis(2,6-diisopropylphenyl)carbodiimide, wherein said pressure-sensitive adhesive composition is optically transparent and, after exposure to a temperature of at least 85°C for 7 days, exhibits an increase in cohesive strength of 0.1 or less as measured by stress relaxation.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylate polymer or copolymer matrix comprises a copolymer matrix that is a reaction product of a (meth)acrylate monomer of formula 1: H2C=CR 1 -(CO)-O-(CH2) a -OH Formula 1 Where R 1 It is an H or methyl group; (CO) is a carbonyl group C=O; and a is an integer from 1 to 5.
3. The pressure-sensitive adhesive composition according to claim 1, wherein the (meth)acrylate polymer or copolymer matrix comprises a copolymer matrix as a reaction product of a (meth)acrylate monomer of formula 1 and at least one additional (meth)acrylate monomer of formula 2: H2C=CR 1 -(CO)-O-(CH2) a -OH Formula 1 Where R 1 It is an H or methyl group; (CO) is a carbonyl group C=O; and a is an integer from 1 to 5. H2C=CHR 1 -(CO)-OR 2 Formula 2 Where R 1 It is a hydrogen atom or a methyl group; (CO) is a carbonyl group C=O; and R 2 It is a hydrogen atom, an alkyl group having 4 to 20 carbon atoms, or an aryl group.
4. The pressure-sensitive adhesive composition according to claim 1, wherein the at least one high-temperature stabilizer comprises thermally stabilized hydrotalcite.
5. The pressure-sensitive adhesive composition according to claim 1, wherein the adhesive composition is optically clear.
6. The pressure-sensitive adhesive composition according to claim 1, wherein the at least one high-temperature stabilizer comprises bis(2,6-diisopropylphenyl)carbodiimide.
7. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the at least one high-temperature stabilizer in the adhesive composition is from 0.1% to 5% by weight.
8. An adhesive article comprising: A substrate, the substrate comprising a first main surface and a second main surface; and An adhesive layer is disposed on the second main surface of the substrate. On at least a portion thereof, said adhesive layer comprises: (Meth)acrylate polymer or copolymer matrix, said (meth)acrylate polymer or copolymer matrix comprising a reaction product of at least one (meth)acrylate monomer containing at least one hydroxyl group; and At least one high-temperature stabilizer, said at least one high-temperature stabilizer comprising thermally stabilized hydrotalcite or bis(2,6-diisopropylphenyl)carbodiimide, wherein said pressure-sensitive adhesive composition is optically transparent and, after exposure to a temperature of at least 85°C for 7 days, exhibits an increase in cohesive strength of 0.1 or less as measured by stress relaxation.
9. The article of claim 8, wherein the (meth)acrylate polymer or copolymer matrix comprises a copolymer matrix that is a reaction product of a (meth)acrylate monomer of formula 1: H2C=CR 1 -(CO)-O-(CH2) a -OH Formula 1 Where R 1 It is an H or methyl group; (CO) is a carbonyl group C=O; and a is an integer from 1 to 5.
10. The article of claim 8, wherein the (meth)acrylate polymer or copolymer matrix comprises a copolymer matrix as a reaction product of a (meth)acrylate monomer of formula 1 and at least one additional (meth)acrylate monomer of formula 2: H2C=CR 1 -(CO)-O-(CH2) a -OH Formula 1 Where R 1 It is an H or methyl group; (CO) is a carbonyl group C=O; and a is an integer from 1 to 5. H2C=CHR 1 -(CO)-OR 2 Formula 2 Where R 1 It is a hydrogen atom or a methyl group; (CO) is a carbonyl group C=O; and R 2 It is a hydrogen atom, an alkyl group having 4 to 20 carbon atoms, or an aryl group.
11. The article of claim 8, wherein the at least one high-temperature stabilizer comprises thermally stabilized hydrotalcite.
12. The article of claim 8, wherein the adhesive composition is optically clear.
13. The article of claim 8, wherein the at least one high-temperature stabilizer comprises bis(2,6-diisopropylphenyl)carbodiimide.
14. The article of claim 8, wherein the content of the at least one high-temperature stabilizer in the adhesive composition is from 0.1% to 5% by weight.
15. The article of claim 8, wherein the substrate comprises a polymer film or a release liner.
16. The article of claim 15, wherein the polymer film comprises an optical film.
Citation Information
Patent Citations
Pressure-sensitive adhesive crosslinked by copolymerizable aromatic ketone monomers
US4737559A
Olefin polymerization catalyst
US5223465A
Two component infrared reflecting film
US5360659A
Acrylamido functional disubstituted acetyl aryl ketone photoinitiators
US5506279A
Antireflection coating for a temperature sensitive substrate
US5579162A